A polyamide with high dielectric properties and high temperature stability and a preparation method thereof

By introducing semi-aromatic nylon segments containing carbonylurea structure into the aliphatic polyamide, the polarization of the dipole is restricted by rigid aromatic blocks, dielectric loss is reduced, and toughness and glass transition temperature are improved by destroying the crystal structure, and the stability of high-temperature use is improved. The problem of insufficient performance of existing dielectric polymers when used at high temperatures is solved, and dielectric polyamides with high dielectric constant, low dielectric loss, excellent mechanical properties and high-temperature use stability are achieved.

CN116425968BActive Publication Date: 2025-04-18SICHUAN LANGDI NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310443057.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-24
Publication Date
2025-04-18
Estimated Expiration
2043-04-24

AI Technical Summary

Technical Problem

Existing dielectric polymers such as BOPP and PVDF have problems with high dielectric loss, poor toughness and low use temperature when used at high temperatures, and interfacial incompatibility in composite dielectric materials will reduce breakdown strength and mechanical strength.

Method used

By introducing semi-aromatic nylon segments containing carbonylurea structure into the aliphatic polyamide, the polarization of the dipole is restricted by using rigid aromatic blocks, dielectric loss is reduced, and toughness and glass transition temperature are improved by destroying the crystal structure, thereby improving the stability of high-temperature use.

Benefits of technology

Dielectric polyamides with high dielectric constant, low dielectric loss, excellent mechanical properties and high-temperature usage stability have been achieved, solving the problem of insufficient performance of existing dielectric polymers when used at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116425968B_ABST
    Figure CN116425968B_ABST
Patent Text Reader

Abstract

The present invention provides a polyamide with high dielectric properties and high temperature stability and a preparation method thereof. The preparation method of the polyamide dielectric film mainly includes the preparation of polyamide salt, aromatic dibasic acid end-capped carbonyl urea, and salt formation with diamine after end-capping, polycondensation reaction and hot pressing molding. In the present invention, the semi-aromatic polyamide salt containing end-capped carbonyl urea and the long-chain nylon salt are copolymerized by high temperature and high pressure. The introduction of the semi-aromatic polyamide containing end-capped carbonyl urea can destroy the regularity of the polyamide, reduce the crystallinity, and improve the transparency; and increase the glass transition temperature, limit the movement of the polyamide molecular chain, so that the strength, toughness and high temperature use stability of the segmented polyamide can be improved at the same time. In addition, the introduction of the semi-aromatic polyamide containing end-capped carbonyl urea can increase the dipole density, but the rigid benzene rings at both ends can limit the rotation of the carbonyl urea dipole during the polarization process, thereby reducing the dielectric loss without losing the dielectric constant. The method of the present invention can effectively reduce the dielectric loss of dielectric polyamide, improve the mechanical strength and transparency, and provide a new idea for increasing the use temperature of dielectric polymers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the synthesis and preparation technology of dielectric polyamide, and in particular relates to the use of aromatic dibasic acid to terminate carbonyl urea, and then to the high-performance dielectric polyamide and the preparation method thereof can be prepared by simple block polymerization. Background Art

[0002] Dielectric polymers are widely used in sensors, brakes, energy storage and other fields because of their good processing performance, light weight, low price and high breakdown strength. Among them, biaxially oriented polypropylene (BOPP) has high breakdown strength and low dielectric loss, and is the most commonly used and large-scale dielectric polymer. However, the dielectric constant of BOPP is low, and the operating temperature is lower than 105°C, which greatly limits the use of BOPP. The dielectric constant of BOPP can be effectively improved by adding dielectric fillers to BOPP to prepare composite dielectric materials, but the interface incompatibility problem in the composite dielectric material will greatly reduce the breakdown strength and mechanical strength of the system, and increase the dielectric loss. In addition, the use temperature of the material cannot be effectively increased by adding fillers. Another commonly used dielectric polymer is polyvinylidene fluoride (PVDF), but the high density of dipoles in PVDF will cause large dielectric losses, and the operating temperature of PVDF is also lower than 105°C, and toxic gases will be released at high temperatures. Therefore, it has become a challenge for scientific research and industry to prepare dielectric polymers with high dielectric constant, low loss, excellent mechanical properties and high-temperature performance.

[0003] Aliphatic polyamides were reported to have ferroelectric properties in 1981 and have the structural characteristics of dielectric polymers. Their dipole moment is 3.7D, which is much higher than that of PVDF. In addition, aliphatic polyamides are of many types, low price, non-toxic, have good mechanical properties, and are simple to prepare and process. They are a class of potential excellent dielectric polymers. For example, polyamide 11 has been shown to have good dielectric properties and is therefore considered to be a substitute for BOPP and PVDF. However, the dipoles with large dipole moments in aliphatic polyamides will undergo orientation polarization in an electric field, resulting in large dielectric losses. In addition, aliphatic polyamides have high crystallinity, so they have poor toughness at low temperatures, and poor mechanical and dielectric properties above the melting point.

[0004] There is no similar solution to the above problem reported in the literature. Block polymers prepared by block polymerization can have the excellent properties of blocks in the molecular chain and will not have interface separation. Therefore, semi-aromatic nylon segments can be introduced into the aliphatic polyamide molecular chain, and carbonyl urea with high dipole density can be introduced into the semi-aromatic nylon structure in order to further increase the dipole density in the molecular chain. Large-volume benzene ring-terminated carbonyl urea can limit the movement of its dipole under the electric field and reduce dielectric loss. The present invention prepares segmented polyamide by introducing semi-aromatic nylon containing carbonyl urea structure into aliphatic polyamide. The semi-aromatic nylon block containing carbonyl urea structure will destroy the regularity of the molecular chain, thereby reducing the crystallinity of the system and improving toughness. At the same time, the conjugation between the benzene ring structures and the hydrogen bonding force between the amide bonds greatly improve the fracture strength of the segmented nylon. In addition, the large rigidity of the aromatic polyamide segment increases the glass transition temperature of the system, thereby improving the high-temperature use stability of the segmented polymer, and the rigid polyamide segment can also limit or even prevent the polarization of the dipole, thereby reducing the dielectric loss of the segmented polyamide. The invention can effectively solve the problems of high dielectric loss, low toughness and low operating temperature of the existing dielectric polyamide. Summary of the invention

[0005] The content of the present invention is to provide a polyamide with high dielectric properties and high temperature stability and a preparation method thereof, so as to solve the problems of high dielectric loss, poor toughness and low operating temperature of existing aliphatic dielectric polyamides. The present invention introduces aromatic blocks of different contents and types into aliphatic polyamides, and limits the polarization of dipoles through rigid aromatic blocks, thereby reducing the loss of the system. In addition, the rigid aromatic blocks destroy the crystallization of the system and increase the glass transition temperature of the molecular chain, thereby improving the toughness and high temperature performance of the system. In order to achieve the above purpose, the present invention provides the following technical solutions: a dielectric nylon film that can be obtained by simple thermal processing, the structural formula is:

[0006]

[0007] x=0.975-0.875,y=0.025-0.125

[0008] The present invention provides a method for preparing a dielectric nylon film that can be prepared by simple thermal processing, comprising the following steps:

[0009] Step 1: biuret and terephthalic acid are subjected to a blocking reaction under high temperature and high pressure conditions to obtain a terephthalic acid blocked biuret product;

[0010] Step 2: Undecanedicarboxylic acid reacts with nonanediamine / terephthalic acid-terminated biuret and decanediamine to form a salt, thereby obtaining a long-chain 911 nylon salt and a semi-aromatic polyamide salt containing carbonyl urea;

[0011] Step 3: adding long-chain 911 nylon salt and semi-aromatic polyamide salt containing carbonyl urea into an autoclave according to a set molar ratio to carry out a pre-polycondensation reaction to obtain a prepolymer; wherein the stirring speed is set to 300 r / min.

[0012] Step 4: The prepolymer obtained in step 3 is heated and vacuumized to continue melt polycondensation, and the small molecular byproduct H2O produced is extracted in time to increase the molecular weight of the polymer.

[0013] Step 5: The nylon copolymer obtained in step 4 is subjected to heat pressing to obtain a copolymerized nylon film. The film thickness is controlled at 40±5 um.

[0014] Furthermore, the salt-forming reaction in step 2 uses water as solvent, the reaction temperature is 80° C., and the pH of the system is controlled to be 7.2 by adding a small amount of reactants during the reaction.

[0015] Furthermore, in step 1, the structural formula of the end-capping product generated by the biuret and terephthalic acid is:

[0016]

[0017] Furthermore, in step 1, biuret, terephthalic acid and water are added together into a polymerization reactor for end-capping reaction, the mass of water added is twice the mass of the reactants, and the mass of terephthalic acid added accounts for 70-80% of the total mass of the reactants.

[0018] Furthermore, in step 1, the reaction temperature of the end-capping reaction is 180° C., the reaction time is 2 hours, the reaction temperature is 200° C., the reaction time is 4 hours, and the reaction pressure is controlled below the saturated vapor pressure of water, specifically 0.5-0.9 MPa.

[0019] Furthermore, in step 1, a catalyst should be added to the end-capping reaction, including phosphorous acid, salts or esters of phosphoric acid, etc., and sodium hypophosphite is preferred in the present invention. An antioxidant is also added to the pre-polycondensation reaction, including antioxidant 1076, antioxidant 1098, etc., and antioxidant 445 is preferred in the present invention.

[0020] Furthermore, in step 2, the structural formula of the 911 salt generated by the reaction of undecanediol and nonanediamine is:

[0021]

[0022] The structural formula of the semi-aromatic polyamide salt containing carbonyl urea generated by the reaction of terephthalic acid-terminated biuret and decanediamine is:

[0023]

[0024] Furthermore, in step 3, the 911 salt obtained in step 2, the semi-aromatic polyamide salt containing carbonyl urea and water are added together into a polymerization reactor for pre-polycondensation reaction, the mass of the added water is twice the mass of the nylon salt, and the molar amount of the added 911 salt accounts for 87.5-97.5% of the total amount of the nylon salt.

[0025] Furthermore, in step 3, the reaction temperature of the pre-polycondensation reaction is 180° C., the reaction time is 2 hours, and the reaction pressure is controlled below the saturated vapor pressure of water, specifically 0.3-0.5 MPa.

[0026] Specifically, in step 3, a catalyst should be added to the pre-polycondensation reaction, including phosphorous acid, salts or esters of phosphoric acid, etc., and sodium hypophosphite is preferred in the present invention. An antioxidant is also added to the pre-polycondensation reaction, including antioxidant 1076, antioxidant 1098, etc., and antioxidant 445 is preferred in the present invention.

[0027] Furthermore, in step 4, the polymerization temperature of the melt polycondensation is 100° C. higher than the melting point, specifically 235° C., the polymerization time is 6 hours, and the vacuum degree is 0.1-0.8 MPa.

[0028] Specifically, in the melt polymerization system in step 4, a circulating water vacuum pump is first used for vacuuming; and then a rotary vane vacuum pump is used for vacuuming.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. The present invention uses terephthalic acid to end-cap biuret. Biuret has a high dipole density and can improve the dielectric constant. At the same time, terephthalic acid with a benzene ring structure is used at both ends of the biuret to limit its orientation movement under an electric field, thereby reducing its dielectric loss, so that the end-capped product can be used as a component with a high dielectric constant and low dielectric loss.

[0031] 2. The present invention selects semi-aromatic polyamide salt containing carbonyl urea to copolymerize with nylon 911 salt. The addition of semi-aromatic polyamide salt chain segments containing carbonyl urea destroys the crystalline structure of PA 911, reduces the crystallinity, and the melting point and crystallization temperature gradually decrease with the increase of 10T content, but the thermal decomposition properties do not change significantly; the direct thermal processing to prepare ferroelectric nylon film is realized.

[0032] 3. The introduction of semi-aromatic polyamide salt containing carbonyl urea improves the rigidity of the chain segment and increases the glass transition temperature of the copolymer, which is conducive to reducing the dielectric loss of the copolymer and improving the thermal stability; at the same time, the delocalized electrons of the π conjugated structure of the rigid benzene ring stabilize the copolymer structure. Conjugation can homogenize the electron density and electrostatic potential distribution of the material and improve the electrical breakdown strength of the material.

[0033] 4. At the same time, the appropriate addition of semi-aromatic polyamide salt containing carbonyl urea also improves the Young's modulus, breaking strength and toughness of the copolymer.

[0034] 5. The copolymer polyamide prepared by the present invention has the advantages of adjustable melting point, high strength, good toughness, easy processing, good heat resistance, low water absorption, etc., and the preparation process is mature and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 This is the infrared spectrum of the polyamide with high dielectric properties and high temperature stability in Example 1.

[0037] Figure 2 This is the DSC graph of the polyamide with high dielectric properties and high temperature stability in Example 2.

[0038] Figure 3 This is the mechanical tensile diagram of the polyamide with high dielectric properties and high temperature stability in Example 2.

[0039] Figure 4 This is a curve diagram showing the change of dielectric constant of the polyamide with high dielectric properties and high temperature stability as a function of frequency in Example 3.

[0040] Figure 5 This is a curve showing the change of dielectric loss versus frequency of the polyamide having high dielectric properties and high temperature stability in Example 3.

[0041] Figure 6 This is a thermal gravimetric curve of the polyamide with high dielectric properties and high temperature stability in Example 3. Specific implementation methods

[0042] The present invention is described in detail below in conjunction with specific embodiments. The exemplary embodiments and descriptions of the present invention are used to explain the present invention, but are not intended to limit the scope of protection of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Case 1

[0044] A method for preparing a polyamide (abbreviated as CoPA-2.5) with high dielectric properties and high temperature stability:

[0045] Step 1: Preparation of end-capped product: weigh 11g (about 0.1mol) of biuret, 50g (about 0.3mol) of terephthalic acid, 3g of sodium hypophosphite, 0.6g of antioxidant 445 and 500ml of deionized water in proportion, mix well and add them into a micro autoclave, seal, evacuate, pass nitrogen, and cycle 5 times. Turn on stirring and set the speed to 300r / min. Heat to 180℃ and react at constant pressure for 2 hours. Heat to 200℃ and react at constant pressure for 4 hours. Turn off heating, wait for the reaction system to cool to room temperature, and take out the product. The product is a white powder.

[0046] Step 2: Preparation of 911 salt, weigh 54g (about 0.25mol) of undecanediol, 39.6g (about 0.25mol) of nonanediamine, and 200ml of deionized water in proportion, mix well and pour into a 500ml three-necked flask. Turn on the stirring device and set the speed to 60r / min, and introduce nitrogen to replace the air in the three-necked flask. Heat to 80℃ for salt formation reaction, and adjust the system pH to 7.2 by adding a small amount of reactants. Stop the reaction after 1 hour of reaction at normal pressure. The obtained 911 salt aqueous solution is rotary evaporated, and then the product is dried under vacuum at 80℃ for 4 hours to obtain 911 salt as a white powder for standby use. The preparation of semi-aromatic nylon salt containing carbonyl urea is prepared by end-capping products and decanediamine by a similar method.

[0047] Step 3: Pre-polycondensation reaction: 14.272g nylon 911 salt, 0.728g semi-aromatic nylon salt containing carbonyl urea, 30g deionized water, 0.015g sodium hypophosphite and 0.045g antioxidant 445 are added to a 100ml tetrafluoroethylene beaker, and the beaker is placed in a micro autoclave, sealed, vacuumed, and nitrogen-filled, and the cycle is repeated 5 times. Stirring is turned on, and the speed is set to 300r / min. The temperature is raised to 180°C and the reaction is carried out at a constant pressure for 2 hours.

[0048] Step 4: Melt polymerization reaction: open the discharge port, release the water vapor in the prepolymerization reaction system to normal pressure, close the discharge port; heat to 235°C, react at constant pressure for 2 hours; vacuumize with a circulating water pump, keep the temperature at 235°C, react for 2 hours; vacuumize with a rotary vane vacuum pump, keep the temperature at 235°C, react for 2 hours. Turn off the heating, wait for the reaction system to cool to room temperature, and take out the product. The product is a white block. Copolyamide film is directly prepared by hot pressing.

[0049] The Fourier transform infrared spectrum (FTIR) of this product is as follows Figure 1 As shown in the figure, it can be seen that the semi-aromatic nylon chain segment containing carbonyl urea has been embedded in the nylon 911 molecular chain, and its melting point has dropped from the melting point of pure nylon 911 187.9℃ to 179.4℃.

[0050] Case 2

[0051] A method for preparing a polyamide (abbreviated as CoPA-5) with high dielectric properties and high temperature stability:

[0052] Step 1: Preparation of end-capped product: weigh 11g (about 0.1mol) of biuret, 50g (about 0.3mol) of terephthalic acid, 3g of sodium hypophosphite, 0.6g of antioxidant 445 and 500ml of deionized water in proportion, mix well and add them into a micro autoclave, seal, evacuate, pass nitrogen, and cycle 5 times. Turn on stirring and set the speed to 300r / min. Heat to 180℃ and react at constant pressure for 2 hours. Heat to 200℃ and react at constant pressure for 4 hours. Turn off heating, wait for the reaction system to cool to room temperature, and take out the product. The product is a white powder.

[0053] Step 2: Preparation of 911 salt, weigh 54g (about 0.25mol) of undecanediol acid, 39.6g (about 0.25mol) of nonanediamine and 200ml of deionized water in proportion, mix well and pour into a 500ml three-necked flask. Turn on the stirring device and set the speed to 60r / min, and introduce nitrogen to replace the air in the three-necked flask. Heat to 80℃ for salt formation reaction, and adjust the system pH to 7.2 by adding a small amount of reactants. Stop the reaction after 1 hour of reaction at normal pressure. The obtained 911 salt aqueous solution is rotary evaporated, and then the product is dried under vacuum at 80℃ for 4 hours to obtain 911 salt as a white powder for standby use. . The preparation of semi-aromatic nylon salt containing carbonyl urea is prepared by a similar method by end-capping the product and decanediamine.

[0054] Step 3: Pre-polycondensation reaction: 13.579g nylon 911 salt, 1.421g semi-aromatic nylon salt containing carbonyl urea, 30g deionized water, 0.015g sodium hypophosphite and 0.045g antioxidant 445 are added to a 100ml tetrafluoroethylene beaker, and the beaker is placed in a micro autoclave, sealed, vacuumed, and nitrogen-filled, and the cycle is repeated 5 times. Stirring is turned on, and the speed is set to 300r / min. The temperature is raised to 180°C and the reaction is carried out at a constant pressure for 2 hours.

[0055] Step 4: melt polymerization reaction: open the discharge port, release the water vapor in the prepolymerization reaction system to normal pressure, close the discharge port; heat to 235°C, react at constant pressure for 2 hours; vacuumize with a circulating water pump, keep the temperature at 235°C, react for 2 hours; vacuumize with a rotary vane vacuum pump, keep the temperature at 235°C, react for 2 hours. Turn off the heating, wait for the reaction system to cool to room temperature, and take out the product. The product is a white block. Copolyamide film is directly prepared by hot pressing. The melting point of the obtained copolyamide is 171.0°C.

[0056] The differential scanning calorimetry (DSC) and mechanical tensile stress-strain curves of the product are shown in Figure 2 and Figure 3 . It can be seen from the figure that with the increase of the content of semi-aromatic nylon containing carbonyl urea, the melting point of the copolymer continues to decrease, from the melting point of pure nylon 911 187.9 ℃ to 171.0 ℃, indicating that the addition of copolymer components destroys the regular semi-crystalline structure of the original nylon 911. At the same time, the introduction of semi-aromatic nylon containing carbonyl urea greatly increases the intermolecular force (hydrogen bond) and the conjugation between benzene rings, thereby increasing the material's fracture strength (from 43.6MPa to 91.29MPa) and toughness (from 78.5MJ / m 3 Increased to 111.3MJ / m 3 ).

[0057] Case 3

[0058] A method for preparing a polyamide (abbreviated as CoPA-10) with high dielectric properties and high temperature stability:

[0059] Step 1: Preparation of end-capped product: weigh 11g (about 0.1mol) of biuret, 50g (about 0.3mol) of terephthalic acid, 3g of sodium hypophosphite, 0.6g of antioxidant 445 and 500ml of deionized water in proportion, mix well and add them into a micro autoclave, seal, evacuate, pass nitrogen, and cycle 5 times. Turn on stirring and set the speed to 300r / min. Heat to 180℃ and react at constant pressure for 2 hours. Heat to 200℃ and react at constant pressure for 4 hours. Turn off heating, wait for the reaction system to cool to room temperature, and take out the product. The product is a white powder.

[0060] Step 2: Preparation of 911 salt, weigh 54g (about 0.25mol) of undecanediol, 39.6g (about 0.25mol) of nonanediamine and 200ml of deionized water in proportion, mix well and pour into a 500ml three-necked flask. Turn on the stirring device and set the speed to 60r / min, and introduce nitrogen to replace the air in the three-necked flask. Heat to 80℃ for salt formation reaction, and adjust the system pH to 7.2 by adding a small amount of reactants. Stop the reaction after 1 hour of reaction at normal pressure. The obtained 911 salt aqueous solution is rotary evaporated, and then the product is dried under vacuum at 80℃ for 4 hours to obtain 911 salt as a white powder for standby use. The preparation of semi-aromatic nylon salt containing carbonyl urea is prepared by end-capping products and decanediamine by a similar method.

[0061] Step 3: Pre-polycondensation reaction: 12.282g nylon 911 salt, 2.718g semi-aromatic nylon salt containing carbonyl urea, 30g deionized water, 0.015g sodium hypophosphite and 0.045g antioxidant 445 were added to a 100ml tetrafluoroethylene beaker, and the beaker was placed in a micro autoclave, sealed, vacuumed, and nitrogen was passed through, and the cycle was repeated 5 times. Stirring was turned on and the speed was set to 300r / min. The temperature was raised to 180°C and the reaction was carried out at constant pressure for 2 hours.

[0062] Step 4: Melt polymerization reaction: open the discharge port, release the water vapor in the prepolymerization reaction system to normal pressure, close the discharge port; heat to 235°C, react at constant pressure for 2 hours; vacuumize with a circulating water pump, keep the temperature at 235°C, react for 2 hours; vacuumize with a rotary vane vacuum pump, keep the temperature at 235°C, react for 2 hours. Turn off the heating, wait for the reaction system to cool to room temperature, and take out the product. The product is a white block. Copolyamide film is directly prepared by hot pressing. The melting point of the obtained copolyamide is 159.1°C.

[0063] The product's dielectric properties vs. frequency curve and thermal gravimetric analysis (TGA) are shown in the figure. Figure 4 , 5 and Figure 6 As shown. It can be seen from the figure that the appropriate content of semi-aromatic nylon containing carbonyl urea reduces the dielectric loss of nylon 911 from 0.055 to 0.033 at a frequency of 100Hz, while still maintaining a high dielectric constant of 3.9. At the same time, the thermal weight loss curve has no obvious change from the original PA911, and the melting point of the comprehensive copolymer is 159.1°C, indicating that the copolymer has good thermal processing properties and a wide processing window. The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A polyamide having high dielectric properties and high temperature stability, characterized in that: The structural formula is: Among them, x=0.975-0.875, y=0.025-0.

125.

2. The method for preparing a polyamide having high dielectric properties and high temperature stability according to claim 1, characterized in that: The steps include: Step 1: performing a capping reaction of biuret and terephthalic acid in a molar ratio of 1:3 under high temperature and high pressure conditions in a nitrogen atmosphere, wherein the stirring speed is set at 300 r / min; Step 2: undecanedicarboxylic acid and nonanediamine / terephthalic acid-terminated biuret and decanediamine in a molar ratio of 1:1 to 1.05 are reacted to form a salt to obtain a long-chain 911 nylon salt and a semi-aromatic polyamide salt containing carbonyl urea; Step 3: adding long-chain 911 nylon salt and semi-aromatic polyamide salt containing carbonyl urea into an autoclave according to different set molar ratios to carry out a pre-polycondensation reaction to obtain a prepolymer, wherein the stirring speed is set to 300 r / min; Step 4: The prepolymer obtained in step 3 is heated and vacuumized to continue melt polycondensation, and the small molecular byproduct H2O produced is extracted in time to increase the molecular weight of the polymer; Step 5: The copolymer polyamide obtained in step 4 is subjected to hot-pressing molding to obtain a copolymer nylon film, and the film thickness is controlled at 40±5 um.

3. The method for preparing a polyamide having high dielectric properties and high temperature stability according to claim 2, characterized in that: In the step 1, the reaction temperature of the end-capping reaction is 180° C.-200° C., the reaction time is 2-4 hours, and the reaction pressure is controlled below the saturated vapor pressure of water, specifically 0.5-0.9 MPa.

4. The method for preparing a polyamide having high dielectric properties and high temperature stability according to claim 2, characterized in that: The structure of the capping product generated by the capping reaction in step 1 is:

5. The method for preparing a polyamide having high dielectric properties and high temperature stability according to claim 2, characterized in that: The salt-forming reaction in step 2 uses water as solvent, the reaction temperature is 80° C., and the pH value after the reaction is 7.

2.

6. The method for preparing a polyamide having high dielectric properties and high temperature stability according to claim 2, characterized in that: In the step 2, the obtained nylon salt aqueous solution is subjected to rotary evaporation to obtain a nylon salt concentrated solution, and the obtained nylon salt concentrated solution is dried.

7. The method for preparing a polyamide having high dielectric properties and high temperature stability according to claim 2, characterized in that: The long-chain 911 nylon salt and the semi-aromatic polyamide salt containing carbonyl urea generated by the salt-forming reaction in step 2 are:

8. The method for preparing a polyamide having high dielectric properties and high temperature stability according to claim 2, characterized in that: In the step 3, when the semi-aromatic polyamide salt containing carbonyl urea, the long-chain nylon 911 salt and water obtained in step 2 are added together into a polymerization reactor for pre-polycondensation reaction, the mass of the added water is twice the total mass of the nylon salt, and the molar amount of the added long-chain nylon 911 salt is 87.5-97.5% of the total molar amount of the nylon salt.

9. The method for preparing a polyamide having high dielectric properties and high temperature stability according to claim 2, characterized in that: In the step 3, the reaction temperature of the pre-polycondensation reaction is 180° C., the reaction time is 2 hours, and the reaction pressure is controlled below the saturated vapor pressure of water, specifically 0.3-0.5 MPa.

10. The method for preparing a polyamide having high dielectric properties and high temperature stability according to claim 2, characterized in that: In step 5, the molding process of the nylon film is first plasticizing at 225° C. for 10 minutes; then hot pressing at 225° C. for 5 minutes at a pressure of 10 MPa; and finally cold pressing at room temperature for 3 minutes at a pressure of 10 MPa.

Citation Information

Patent Citations

  • Copolymerized polyamide capable of preparing ferroelectric nylon film through simple hot processing, and preparation method thereof

    CN111635522A

  • Film of copolymer of long-chain nylon and preparation method of film

    CN113999389A